Marx and Digital Machines Alienation, Technology, Capitalism - Healy, Mike (University of Westminster Press, 2020)
"This book explores the fundamental contradiction at the heart of the digital environment: technology offers all manner of promises, yet habitually fails to deliver. This failure often arises from numerous problems: the proficiency of the technology or end-user, policy failure at various levels, or a combination of these. Solutions such as better technology and more effective end-user education are often put into place to solve these failures. Mike Healy argues that such approaches are inherently faulty drawing upon qualitative research informed by Marx's theory of alienation. Using Marx's theory, he considers participants in three distinct settings: the workplace of information and communications technology (ICT) professionals; university scholars researching the ethical and societal implications of our digital environment; and a group of pensioners living in South London, UK, undertaking ICT training. By delving beneath the surface of how digital technologies are created, researched and experienced, this study illustrates the contradictory nature of our digital lives, as they directly arise from the needs of capitalism. The book also places Marx's theory in contrast to the mainstream approaches derived from Seaman and Blauner. In researching and comprehending ICT, this book reaffirms the superior explanatory power of Marx's theory of alienation."